(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
A revolutionary progress in the 21st century for the wireless and mobile communication industry has influenced the improvement of modern communication equipment. Such equipments are having an ultra-compact size with many features. The basic element in wireless communication has experienced incredible improvements specifically in the track of compactness and broad bandwidth. In the radio frequency range the antennas design and usage are prominent. Since the handsets are having a limited space it is difficult to install more than one antenna. To overcome these problems, the fractal shaped antennas are designed and studied. A structure of fractal is an uneven or fragmented geometric shape that can be fragmented into parts, each of which is a reduced size copy of whole. The shapes of fractals do not have characteristic size. Each fractal consists of multiple iterations of a single fundamental shape. The repetitions can continue infinitely, to get a shape within a finite boundary for an infinite length or area. The fractal antennas have a finite structure at arbitrary small scales, are difficult to describe in traditional Euclidean geometries and their construction and design is simple and recursive.